Mass spectrometry analysis of nucleosides and nucleotides. Issue 4 (27th November 2013) - Dudley, Ed; Bond, Liz
Abstract Mass spectrometry has been widely utilised in the study of nucleobases, nucleosides and nucleotides as components of nucleic acids and as bioactive metabolites in their own right. In this review, the application of mass spectrometry to such analysis is overviewed in relation to various aspects regarding the analytical mass spectrometric and chromatographic techniques applied and also the various applications of such analysis. © 2013 Wiley Periodicals, Inc. Mass Spec Rev 33: 302–331, 2014.